2019
DOI: 10.1108/bfj-07-2019-0478
|View full text |Cite
|
Sign up to set email alerts
|

Millennial generation preferences for rosé wine

Abstract: Purpose The purpose of this paper is to verify the preferences for the purchase of rosé wine by Italian and French Millennials, with the aim of allowing Italian companies to acquire knowledge in improving the positioning of this product in both the Italian and French markets. Design/methodology/approach The study involved a descriptive survey conducted between December 2018 and January 2019 on Millennials residing in Italy and France, intercepted via Facebook. In total, 500 valid responses to a highly struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…The only cross-criterion is food, culture and nation. This is not surprising as previous research clearly shows that such elements play an important role in marketing, but also for consumers' ability to relate to the product (Iaia et al, 2018;Iazzi et al, 2020;Maizza et al, 2017). For Georgia, legitimation is essential, because the wine market is highly competitive, but also because this is an old trade, consumers have a previous relation to the 'old and the new world'.…”
Section: Stories and Archetypesmentioning
confidence: 89%
See 2 more Smart Citations
“…The only cross-criterion is food, culture and nation. This is not surprising as previous research clearly shows that such elements play an important role in marketing, but also for consumers' ability to relate to the product (Iaia et al, 2018;Iazzi et al, 2020;Maizza et al, 2017). For Georgia, legitimation is essential, because the wine market is highly competitive, but also because this is an old trade, consumers have a previous relation to the 'old and the new world'.…”
Section: Stories and Archetypesmentioning
confidence: 89%
“…Previous research shows that Millennials is an important group of wine consumers (Iazzi et al, 2020), however, only a few companies in the sample have products that address this segment separately, instead markets are addressed based on address, rather than preferences. The domestic market is seen as uniform in relation to quality preferences, price, age and product knowledge.…”
Section: Managerial Implications and A New Market For Historical Winesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, through the label, the sustainable attributes of the wine are communicated, which play a relevant role in the millennial wine purchase decision-making process [31,34]. Furthermore, wine business research suggests that the importance attached to price by this consumer group is directly correlated, among others, to their country of origin [37], the wine production system [34] or wine type [44].…”
Section: Millennial Wine Consumption Habitsmentioning
confidence: 99%
“…Notwithstanding potential limitations, a 5-point Likert scale was found suitable for the present study proposal. Th is number of items has been used in recent similar wine studies [15,19,44]. It has been suggested that this number can reduce respondent's frustration [51],and is also related to an increased response rate [52].…”
Section: Task and Proceduresmentioning
confidence: 99%